Does the trimline extension and attachment size affect maxillary arch expansion in clear aligner therapy ? A finite element study - Karsli Nurver; Yildirim Fazilet; Dingiloğlu Arda; Özsoy Ömür Polat (Sciendo, 2024)
Using finite element analysis (FEA), the aim of the present study was to evaluate the effects of different aligner trimline extensions and attachment sizes on maxillary first and second molars under expansive forces delivered by clear aligner therapy